Javier Sologuren and Japanese literature - Derteano Galdos, Pilar (2016)
This article explores the intertextual connection between essays and poetic exploration of Javier Sologuren and Japanese classics literature. From his first encounter with the Japanese artistic expression, he pours into his studies and collections of poems to the best of his knowledge.  Which relationship deepening on between his Folios de El enamorado y la muerte (1980; Folios form the Lover and Death) and the brief narrative of Yasunari Kawabata; the usage of haiku and the fragmentary weaving perceptions and memories; as well as, the thematic proximity with the concerns of the contemporary trend of the new Japanese sensibility.